ANALISIS BENEISH M-SCORE UNTUK MENDETEKSI FINANCIAL STATEMENT FRAUD PADA PT. GARUDA INDONESIA Tbk PERIODE 2017-2019 - Julianto, Dedi; Marjono, Marjono; Labangge, Aminullah (Jurnal Ekonomi STIEP ( JES ), 2021)
This study aims to detect financial statement fraud at PT. Garuda Indonesia in 2017-2019 used the Beneish M Score model and testing whether the Beneish M Score model can detect the occurrence of financial statement fraud at PT. Garuda Indonesia in 2018. The results of this study indicate that PT Garuda Indonesia was classified in the Gray criteria, that can be interpreted as manipulate or not manipule financial statements in 2017 and 2018 and classified in the criteria not manipulate financial statements in 2019. The results of this study also found that the Beneish M Score model could not accurately to detect the manipulation of financial statements at PT. Garuda Indonesia in 2018, because only two ratios are Gross Margin Index (GMI) and Days Sales in Receivable Index (DSRI) which detect manipulation of financial statements, so they are only classified in the gray area criteria